Making the ropes: How daily practices in a booming periurban municipality become durable 'gray' institutions shaping land use. (June 2023) - Baird-Zars, Bernadette
Abstract: Predictable unwritten rules arguably are at the heart of all land development processes. How do these practices emerge and remain in local land governance? While municipal land use offices are increasingly one of the few remaining formal spaces for the state to review and negotiate legal urbanization in Mexico and many other contexts, literatures on implementation in local policy and development in Mexico and the South are nascent, and typically bypass both daily practices and municipal offices as arenas for meaningful institutional emergence or intervention. This article examines how land use officials developed and sustained a small set of repeating daily practices managing requests for development in Tlajomulco de Zúñiga, a rapidly growing outskirt of Guadalajara, Mexico. A sociological-institutionalist approach draws on ethnographic and case study methodologies to examine material from over 40 interviews and 25 hours of observation in the land use permitting department of Tlajomulco as well as internal documents, official laws and plans, and media accounts. The resulting analysis suggests that Tlajomulco's land use officials developed and sustained a broad array of legal yet informal patterns of daily practice ('gray institutions') in part through an unusual fifteen-year period of relative staff continuity. The land use staff also took strategic actions to increase the strength of their gray institutions: these included maintaining discourses of valuing collective knowledge and pride in 'tinkering', promoting skills and abilities to engage with formal regulations, and mediating their relational networks through strategic downplaying of their power and knowledge. Centering institutionalized practices of local land use offices such as Tlajomulco -and outlining how they emerge and remain- can help planners better understand the processes of planning 'as it happens', chart arenas of localized innovation and improvisation, and expand the terrains of decentered planning knowledge and land use implementation. Highlights: land use officials develop and sustain legal yet informal patterns of daily practice. "gray institutions" mediate implementation of land use plans and regulation. valuing collective knowledge and strategic downplaying helps institutions survive. unpacking a municipal 'black box' reveals everyday tools to shift periurban sprawl. facing extreme growth, street-level bureaucrats improvised and innovated in teams.